2007
DOI: 10.1523/jneurosci.4119-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Extracellular Signal-Regulated Protein Kinase 1/2 with Actin Cytoskeleton in Supraoptic Oxytocin Neurons and Astrocytes: Role in Burst Firing

Abstract: Neuronal firing patterns determine the manner of neurosecretion, the underlying mechanisms of which are poorly understood. Using supraoptic nuclei in brain slices from lactating rats, we examined the involvement of extracellular signal-regulated protein kinase 1/2 (ERK1/2) and filamentous actin (F-actin) in burst generation by oxytocin (OT) neurons. Blocking phosphorylation of ERK1/2 (pERK1/2) decreased miniature EPSCs and blocked OT-evoked bursts, as did intracellularly loading an antibody against pERK1/2. OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 47 publications
10
76
0
2
Order By: Relevance
“…In previous work, we found that suckling changed astrocytic morphology (Wang and Hatton, 2007b), which is usually associated with GFAP plastic changes (Weinstein et al, 1991). Thus, we further observed effects of intracerebroventricular application of L-AAA and fluorocitrate on GFAP expression in the SON.…”
Section: Rapid Changes In Gfap Plasticity During Sucklingsupporting
confidence: 73%
See 4 more Smart Citations
“…In previous work, we found that suckling changed astrocytic morphology (Wang and Hatton, 2007b), which is usually associated with GFAP plastic changes (Weinstein et al, 1991). Thus, we further observed effects of intracerebroventricular application of L-AAA and fluorocitrate on GFAP expression in the SON.…”
Section: Rapid Changes In Gfap Plasticity During Sucklingsupporting
confidence: 73%
“…In observing effects of suckling on GFAP expression, immunocytochemistry was performed as described previously (Hatton et al, 1987;Wang and Hatton, 2007b) with minor modification. In brief, hypothalamic slices containing the SON were permeated with 0.3% Triton X-100 for 30 min, and nonspecific binding sites to antibodies were blocked by incubation of the sections in 0.3% gelatin for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations